Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 68. Beitrag. Hymenoptera: Apidae III (Genus Nomada Scopoli). - Schwarz, Maximilian (Contributions to Entomology = Beiträge zur Entomologie, 1967)
The present paper is concerned with the Nomada (Apoidea) collected by the expedition to Albania by Deutsches Entomologisches Institut. It covers 29 specimens of 12 species, one species being new: Nomada lucidula spec. nov., which is also known from Greece, Turkey and Israel. The hitherto unknown male of Nomada pastoralis Eversmann is described. The infrequent references to the Nomada of Albania made in previous publications were ignored, as those data might be evaluated only if the respective specimens were examined. Nomenclatural Acts lucidula Schwarz, 1967 (Nomada), spec. n.